Вы находитесь на странице: 1из 13

Solutions by:

Johannes Hofmann Laurence Perreault Levasseur David Morris Marcel Schmittfull

Quantum Field Theory Example Sheet 1 Michelmas Term 2011

jbh38@cam.ac.uk

L.Perreault-Levasseur@damtp.cam.ac.uk

dmm49@cam.ac.uk

M.Schmittfull@damtp.cam.ac.uk

Note: In the conventions of this course, the Minkowski metric is g = diag (1 , 1, 1, 1), or ‘mostly minus.’

Exercise 1

Lagrangian:

Express y (x, t) as a Fourier series:

L = a dx σ

2

∂y

∂t

0

2 T

2

∂y x 2

y (x, t) =

2

a

=1 q n (t ) sin nπx .

n

a

The derivative of y (x, t) with respect to x and t is

∂y (x, t) ∂t

∂y (x, t) ∂x

=

=

2

a

2

a

=1 q˙ n (t ) sin nπx

n

a

a

q n (t ) cos nπx ,

a

n

=1

(1)

(2)

(3)

(4)

where we abbreviate q˙ ∂q/∂t . Substituting Eqs. (3 ) and (4) in (1) gives

L =

n,m a

1

a

0

dx

σ q˙ n (t )q˙ m (t ) sin nπx sin mπx

a

a

T nmπ 2

a

2

q n (t )q m (t ) cos nπx cos mπx .

a

a

Using the orthonormality relations

2

a a

0

2

a a

0

dx

dx

sin nπx sin mπx =

a

a

δ

nm

cos nπx cos mπx = δ nm

a

a

and

we see that the terms with n = m vanish. We obtain:

L =

n

a

0

dx

σ

2

q˙

n (t ) T

2

2

a

2 q n (t ) .

2

The Euler-Lagrange equations are given by

With

we obtain the equations of motion:

d

∂L ∂L

dt

∂ q˙ n

∂q n

= 0,

n = 0, 1 , 2,

∂L

q˙ n

∂L

∂q

n

= σ q˙ n

and

= T nπ 2 q n

a

q¨ n (t ) + T

σ

a

2 q n (t ) = 0 ,

where n = 0, 1, 2,

These are the equations of motion of harmonic oscillators with frequency ω n = nπ

a

T

σ .

1

(5)

(6)

(7)

(8)

(9)

(10)

(11)

(12)

Exercise 2

The scalar ﬁeld φ(x) transforms under a Lorentz transformation x µ x µ = Λ µ ν x ν as

φ(x) φ (x ) = φ(x) = φ1 x ).

Note that this is an active transformation, i.e. the new ﬁeld at the new coordinate equals the old ﬁeld at the old coordinate. Using

Now,

µ

∂x µ

µ µ φ(x) + m 2 φ(x)

= ∂x ν

∂x µ

x ν = (Λ 1 ) ν µ ν

µ µ φ (x ) + m 2 φ (x )

= g µν 1 ) ρ µ ρ 1 ) κ ν κ φ(x) + m 2 φ(x)

= g ρκ ρ κ φ(x) + m 2 φ(x).

(13)

In the last step we used that Λ is a Lorentz transformation and so its inverse Λ 1 preserves the inverse Minkowski metric g µν ,

1 ) ρ µ g µν 1 ) κ ν = g ρκ .

Eq. (13 ) therefore demonstrates that if φ(x) fulﬁls the Klein-Gordon equation

then φ1 x) likewise fulﬁls it.

Exercise 3

Lagrangian density:

Euler-Lagrange equation for φ :

With

We obtain the equation of motion for φ :

µ µ φ(x) + m 2 φ(x) = 0 ,

L = µ φ µ φ m 2 φ φ λ (φ φ) 2 .

2

L µ

∂φ

L

(µ φ )

= 0.

L

∂φ

= m 2 φ λ (φ φ)φ

L

( µ φ) = µ φ.

and

µ µ φ + m 2 φ + λ (φ φ)φ = 0.

(14)

(15)

(16)

(17)

(18)

Similarly, we can calculate the ﬁeld equation for φ. The result is the complex conjugate of Eq. (18 ).

Consider the U(1) transformation

φ(x) e iα φ(x),

and φ (x) e iα φ (x),

(19)

where α [0, 2π ) is a constant. It is straightforward to check that the Lagrangian ( 14 ) is invariant under this transformation. This is an example of a global symmetry, i.e., the symmetry transformation acts in the same way on the ﬁelds at each point in space and time.

The inﬁnitesimal transformation of (19) is:

φ φ + δφ,

φ φ + δφ ,

where δφ = iαφ,

δφ = iαφ.

and

(20)

(21)

We can check explicitly that the Lagrangian density is invariant under this transformation:

δ L = µ (δφ )µ φ + µ φ µ (δφ ) m 2 (δφ φ + φ δφ ) λ (φ φ)(φ δφ + δφ φ)

= iα∂ µ φ µ φ + iα∂ µ φ µ φ + iαm 2 (φ φ φ φ) iαλ (φ φ)(φ φ φ φ) = 0 .

2

(22)

According to Noether’s theorem, a global symmetry implies the existence of a conserved current. If L → L + α L, where ∆ L = µ J µ , then the conserved Noether current is given by the formula (Schroeder & Peskin p. 18)

j µ =

( µ L φ a ) φ a − J µ ,

(23)

where a labels all the ﬁelds in the theory. In this case there are two independent ﬁelds φ and φ , and

The conserved current is thus

φ = iφ ,

φ = iφ ,

L = 0 .

j µ =

( L µ φ) () +

L

(µ

φ ) ( )

= i {φ (µ φ) (µ φ )φ} .

(24)

Notice that this quantity is real, and we can check explicitly that it is indeed conserved:

 ∂ µ j µ = −i (φ ∗ ∂ µ (∂ µ φ) − (∂ µ φ ∗ )(∂ µ φ) + (∂ µ φ ∗ )(∂ µ φ) − ∂ µ (∂ µ φ ∗ )φ) = −i (φ ∗ ∂ µ (∂ µ φ) − ∂ µ (∂ µ φ ∗ )φ) = −i φ ∗ −m 2 φ − λ (φ ∗ φ)φ − −m 2 φ ∗ − λ (φ ∗ φ)φ ∗ φ = 0.

(25)

In the last step, we used the equation of motion for φ and φ , Eq. (18).

Exercise 4

The Lagrangian will certainly be invariant under SO(3) rotations of the ﬁelds φ a , a = 1, 2, 3, since only the ‘length’ φ a φ a enters the Lagrangian. Inﬁnitesimally, consider the transformation of φ a φ a under a rotation of the ﬁelds φ a by an inﬁnitesimal angle θ

(26)

φ a φ a + θ abc n b φ c , i.e. ∆ φ a = abc n b φ c

where n a is a constant unit vector. φ a φ a transforms as

(φ a + θ abc n b φ c )(φ a + θ ade n d φ e )

φ a φ a

= φ a φ a + θ abc n b φ c φ a + θ ade n d φ e φ a + O (θ 2 )

= φ a φ a + O (θ 2 ).

In the last step we used that abc is skew-symmetric under exchange of c and a whereas φ c φ a is symmetric under this exchange, and therefore the sum vanishes. The same applies to the other term linear in θ . Dropping the θ 2 term we ﬁnd that φ a φ a is indeed invariant under (26). Similarly one can also show that µ φ a µ φ a is invariant under (26). Therefore L is invariant under ( 26).

To obtain the associated Noether current, we refer to the formula (23) above. In our case J = 0 and ∆ φ a = abc n b φ c , so that

j µ = (µ φ a ) abc n b φ c .

The Noether current j µ implies a conserved charge

˙

Q d 3 x j 0 = d 3 x

˙

φ a abc n b φ c .

This is conserved ( Q = 0) for any unit vector n . If we choose n b = δ bd for d = 1, 2, 3 (i.e. n is any of the standard basis

vectors of R 3 ), we obtain three linearly independent charges

Q d = d 3 x adc φ a φ c = d 3 x dac φ a φ c .

˙

˙

Let us ﬁnally show explicitly that these charges are conserved using the equations of motion. These are given by

Then we get

µ µ φ a

¨

+ m 2 φ a = φ a − ∇ 2 φ a + m 2 φ a = 0.

d

dt Q a

=

=

d

dt d 3 x abc φ b φ c

˙

d 3 x abc ( φ b φ c +

¨

˙

φ

b

˙

φ

c )

=

d 3 x abc ( φ b φ c )

¨

= d 3 x

abc 2 φ b φ c m 2 φ b φ c

= d 3 x abc φ b · ∇ φ c = 0.

3

Here we used the skew-symmetry of the tensor several times and integrated by parts to go to the last line. We assume that the ﬁeld falls oﬀ suﬃciently fast so that we can neglect the boundary term of the partial integration.

Exercise 5

Under a Lorentz transformation, the vector x µ transforms as:

 x µ → x µ = Λ µ ν x ν ; (27) and such transformations leave invariant the form g µν x µ x ν = g µν x µ x ν . (28) Replacing the x µ s by their deﬁnition in terms of Λ µ ν , g µν x µ x ν = g µν (Λ µ α x α ) Λ ν β x β = g µν Λ µ α Λ ν β x α x β = g αβ Λ α µ Λ β ν x µ x ν . (29)

In the last step, we have interchanged the indices α and β with µ and ν . Now, equating (28) with the last step in ( 29), it follows straightforwardly that:

 g µν = g αβ Λ α µ Λ β ν (30) Now, let us consider an inﬁnitesimal Lorentz transformation of the form: Λ µ ν = δ µ ν + ω µ ν ; |ω | 1 (31) Using (30), we ﬁnd that, keeping only the terms up to ﬁrst order in ω : g µν = δ α µ + ω α µ g αβ δ β ν + ω β ν = g µν + ω µν + ω νµ + O ω 2 , (32)

which requires that ω µν is an antisymmetric tensor for the above transformation to indeed be a Lorentz transformation.

For those of you who are interested in such matters, we introduce an alternative, more mathematically sound means of thinking about the concept of an ‘inﬁnitesimal’ Lorentz transform. Consider a one-parameter family of Lorentz transfor- mations, that is a diﬀerentiable function Λ : R SO(3 , 1), i.e. for each value of the parameter t , Λ ( t ) deﬁnes a Lorentz transformation. Take the family so-deﬁned to be such that Λ(0) = I, the identity.

Then for all t ,

g µν = g αβ

Λ( t ) α µ Λ( t ) β ν .

(33)

Looking ‘inﬁnitesimally’ corresponds to diﬀerentiating at the identity, i.e. consider

dt g αβ Λ( t ) α µ Λ( t ) β ν t=0

d

However, according to (33), this is precisely

 = g αβ Λ (0) α µ Λ(0) β ν + g αβ Λ(0) α µ Λ (0) β ν = g αν Λ (0) α µ + g µβ Λ (0) β ν .

d

dt g αβ Λ( t ) α µ Λ( t ) β ν

t=0

=

d

dt g µν

t=0

= 0.

Therefore, if we deﬁne a matrix ω by

ω α µ = Λ (0) α µ ,

we have in all that

0 = g αν ω α µ + g µβ ω β ν = ω νµ + ω µν .

To make the connection with our earlier ‘inﬁnitesimal’ form of the Lorentz transformation Λ µ ν , we can write down the Taylor expansion of Λ(t ) for t small,

 Λ( t ) µ ν = Λ(0) µ ν + t Λ (0) µ ν + O (t 2 ) = δ µ ν + t ω µ ν + O (t 2 ).

Besides being completely rigorous, the beneﬁt of this approach is that Λ inﬁnitesimal is characterized by a parameter t being small, while ω µν is any skew-symmetric matrix and not an inﬁnitesimal object. One-parameter families of transformations, and in particular one-parameter subgroups (i.e. smooth homomorphisms Λ : R G ), are precisely how one deﬁnes the Lie algebra of a group and its exponential map in a more general setting - i.e. when the group isn’t given as being embedded in Gl(n, R ).

The form of the inﬁnitesimal rotations and boosts are given by:

4

Rotation:

A generic rotation by an angle θ about the x 3 -axis is given by:

1

0

0 sin θ

0

0

cos θ

0

0

sin θ

cos θ

0

0

0

0

1

.

(34)

Taylor expanding the trigonometric functions up to ﬁrst order in θ , we ﬁnd that an inﬁnitesimal rotation around the x 3 -axis is given by:

δ µ ν + ω µ ν = δ µ ν + θ

0

0

0

0

0

0

1

0

0

1

0

0

0

0

0

0

.

As a check on the above, exponentiate the matrix

ω = θ

0

0

0

0 0

0

0

1

0

1

0

0

0

0

0

0

.

 In order to do this, calculate that so that

ω 2 = θ 2

0 0

0

0

0

0

0

1

0

0

1

0

0

0

0

0

,

 

ω 2 k = (1) k θ 2 k

0

0

0

0

0

1

0

0

0

0

1

0

This facilitates the calculation

exp ( ω ) = I +

=

0

0

0

0

 

k =1

1

0

0

0

1

ω 2 k +1 = (1) k θ 2 k +1

 

1

(2k + 1)! ω 2 k +1

k

=0

2k ! (1) k θ 2 k

1

0

0

0

0

,

k 1

2 k ! ω 2 k +

0

0

0

0

0

0

0

0

0

0

0

1

k =1

+

+

k =1

 

(2k + 1)! (1) k θ 2 k +1

1

0 0

0 0

0

0 0

1

0

1

0

0

0

0

0 1

0

0

0 0

0

0

0

0

0

1

0

0

0

0

1

0

,

0

1

0

0

0

0

0

0

0

0

0

0

 

,

k 0

(35)

and the desired expression for this ﬁnite transformation follows from identifying the two series here as, respectively, cos θ and sin θ .

Boost:

A generic boost along the x 1 -axis is given by:

γ

γv

0

0

γv

γ

0

0

0

0

1

0

0

0

0

1

.

(36)

Recall that the rapidity φ is deﬁned via tanh φ = v , so that the above boosts are parameterized by

cosh φ sinh φ

0

0

sinh φ 0

0

1

0

cosh φ

0

0

5

0

0

0

1

.

(37)

Taylor expanding to ﬁrst order around φ = 0 (i.e. v = 0), the inﬁnitesimal boost by v is found to be

δ µ ν + ω µ ν = δ µ ν + φ

0

1

0

0

1

0

0

0

0

0

0

0

0

0

0

0

.

(38)

Again, we check that the above ‘inﬁnitesimal’ transformation gives the correct ﬁnite transformation when we exponen- tiate the matrix

Again, calculate the square

so that the even and odd powers are

ω 2 k = θ 2 k

1

0

0

0

0

1

0

0

0

0

0

0

This facilitates the calculation

0

0

0

0

ω = φ

0

1

0

0

ω 2 = φ 2

,

k 1

1

0

0

0

1

0

0

0

0

1

0

0

0

0

0

0

0

0

0

0

0

0

0

0

0

0

0

0

.

,

ω 2 k +1 = θ 2 k +1

0

1

0

0

exp ( ω ) = I +

k

=1

1

2k ! ω 2 k +

k

=1

1

(2k + 1)! ω 2 k +1

=

0

0

0

0

0

0

0

0

+

k =1

0

0

1

0

0

0

0

1

+

k

=0

2k ! θ 2 k

1

 

(2k + 1)! θ 2 k +1

1

0

1

0

0

1

0

0

0

1

0

0

0

0

0

0

0

1

0

0

0

0

0

0

0

0

1

0

0

0

0

0

0

0

0

0

0

 

,

0

0

0

0

0

0

0

0

,

k 0

and the desired expression follows from identifying the two series here as, respectively, cosh φ and sinh φ.

Mathematical Remark: As was pointed out by some of you in class, there is some subtlety involved in the above operations:

1. If one takes a group, is it true that exponentiating (a representation of) its algebra gives an element of (a representation of) the original group? Seen from a diﬀerent perspective, can two groups have the same algebra?

2. If the answer to the previous question is positive, can one obtain all elements in this way?

Unfortunately, the answer to both of these questions is in the negative. Fortunately, the answer is almost as nice as one would wish, and is certainly much more interesting than a bland aﬃrmative.

Aspects of the relevant theory may be covered in the course ‘Symmetries and Particles’ and is covered in the course ‘Lie Algebras and Their Representations,’ though, needless to say, in great abstraction. Otherwise, see Warner, Foundations of Diﬀerentiable Manifolds for general background or Fulton & Harris, Representation Theory for full details.

Exercise 6

From the previous exercise, a four-vector x µ transforms under an inﬁnitesimal Lorentz transformation as

x µ x µ = Λ µ ν x ν = x µ + t ω µ ν x ν + O (t 2 ) , t small .

Similarly, a scalar ﬁeld φ transforms according to

φ(x) φ (x ) = φ Λ 1 x .

6

(39)

(40)

We need to know what Λ 1 looks like ﬁnitesimally. From the deﬁnition (30), the inverse to any Lorentz transformation Λ is simply

Λ 1 µ ν = g µα g νβ Λ β α .

Note that if the metric were Euclidean, this would simply say Λ T = Λ 1 . In our case, the inverse to the above inﬁnitesimal transformation is (neglecting terms at order t 2 )

1 ) µ ν

=

=

=

= δ µ ν t

t

δ µ ν

δ µ ν

+

+ t ω να g µα

ω β α g µα g νβ

ω αν g µα

ω µ ν ,

δ µ ν t

 (42) In the second line we use the skew-symmetry of ω να . Now, Taylor expanding φ to ﬁrst order in t , we obtain: φ(x µ ) → φ (x µ ) = φ(x µ ) − t ω µ ν x ν ∂ µ φ(x µ ). (43)

The Lagrangian density, L, is a Lorentz scalar and will therefore transform in a like manner to φ under an inﬁnitesimal Lorentz transformation:

L(x µ ) −→

L(x µ ) = L(x µ ) t ω µ ν x ν µ L(x µ )

Hence, δ L = t ω µ ν x ν µ L. If you are unconvinced by this reasoning, check explicitly that the Lagrangian for scalar ﬁeld theory, given the transformation for φ, does indeed change in this way.

However,

µ (ω µ ν x ν L) =

µ (ω µ ν x ν ) L + ω µ ν x ν µ L

= ω µ ν µ (x ν ) L + ω µ ν x ν µ L

ω µ ν δ L + ω µ ν x ν µ L

=

=

µ

ν

ω µ ν x ν µ L;

(44)

where in the second step we have used that ω µ ν is a constant tensor, and in the last step we made use of the skew-symmetry of ω µν to infer that ω µ µ = 0. Therefore, we obtain that the variation of the Lagrangian density is a total derivative:

L = µ (ω µ ν x ν L)

.

(45)

There is a conserved current associated with the above symmetry, given by the formula (23) from earlier. Inserting the expressions derived above for ∆ φ and J µ , we obtain:

j µ

= ω α β x β

L (µ

φ) α φ δ µ α L

According to the standard deﬁnition in ﬁeld theory, the bracketed quantity is precisely the energy-momentum tensor, T µ

α

.

The total charge Q is given by:

Q d 3 x j 0

= d 3 x ω µ ν x ν T 0 µ .

For pure spatial rotations, take ω i j = 0, else ω µ ν = 0. In this case:

Q

=

=

d 3 x

d 3 x

ω j k x k T 0

j

ω jk x k T 0 j

= d 3 x

1

2

ω jk x j T 0 k x k T 0 j

= d 3 x x j T 0 k x k T 0 j

ω jk

2

(46)

(47)

(48)

7

In the third line the skew-symmetry was used to throw away the symmetric part of x k T 0 j .

Any skew 3 × 3 array ( ω jk ) may be written uniquely as a linear combination of the three skew matrices ω i deﬁned via (ω i ) jk = ijk . We therefore obtain three linearly independent charges

Q i = ijk

2 1 d 3 x x j T 0 k x k T 0 j ,

which have the interpretation of angular momenta.

(49)

For a Lorentz boost along the x i direction, set ω 0 k = δ ik and ω µ ν = 0 otherwise. This implies ω k 0 = δ ik also, since

(using our metric conventions)

Therefore, in this case:

ω k 0 = ω k 0 = ω 0 k = ω 0 k = δ ik

Q i

 = − d 3 x ω 0 k x i T 0 0 − d 3 x ω k 0 x 0 T 0 k = − d 3 x x i T 0 0 − x 0 T 0 0 = d 3 x x 0 T 0 i − x i T 00

where to arrive at the ﬁnal expression we raise the indices 0 and i in each term picking up factors of +1 and 1, respectively.

Since Q i is conserved, taking its derivative with respect to time gives zero:

d

dt Q i = 0 0 =

dt d 3 x x 0 T i 0 dt d 3 x x i T 00

d

d

= d 3 x T i 0 + t d 3 x

d

dt T i 0

dt d 3 x x i T 00 = d 3 x T i 0 + t d 3 x dt T i 0

d

d

dt d 3 x x i T 00

d

(50)

(51)

(52)

(53)

To interpret this equation, recall now that T 00 is the energy density of the quantum ﬁeld and that T 0 k is its linear momentum density. The ﬁrst term on the right-hand side is the total (physical) linear momentum (i.e. the space integral of the linear momentum density) and it is therefore conserved by conservation of momentum. Similarly, the last term on the RHS vanishes since the linear momentum is conserved. Therefore, we ﬁnd that the LHS is a constant.

Concerning its interpretation, we ﬁnd that the center of energy of the ﬁeld travels with constant speed. We can see from the fact that the spatial integral indicates some average position of the energy of the ﬁeld.

Exercise 7

In Maxwell Theory, the dynamics of a co-vector ﬁeld A µ (x) are governed by the Lagrangian

L =

1

4 F µν F στ η µσ η ντ = 1 4 F µν F µν

in terms of the ﬁeld-strength (or Faraday) tensor

Under the ‘gauge’ transformation

F µν =